2006
DOI: 10.1111/j.1742-7843.2006.pto_303.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants and Risk of Upper Gastrointestinal Bleeding

Abstract: Selective serotonin reuptake inhibitors (SSRIs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 38 publications
1
49
1
3
Order By: Relevance
“…Pharmacodynamically, SSRIs could interact with acenocoumarol since the release of serotonin by platelets plays an important role in haemostasis [44,45]. This mechanism has not been clearly explained, but recent epidemiological data have demonstrated that SSRIs could significantly increase the risk of gastro-intestinal bleeding [46,47]. According to some studies, the use of SSRIs among the population treated with coumarins seems to place patients at an increased risk of bleeding [15,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacodynamically, SSRIs could interact with acenocoumarol since the release of serotonin by platelets plays an important role in haemostasis [44,45]. This mechanism has not been clearly explained, but recent epidemiological data have demonstrated that SSRIs could significantly increase the risk of gastro-intestinal bleeding [46,47]. According to some studies, the use of SSRIs among the population treated with coumarins seems to place patients at an increased risk of bleeding [15,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…hemoptizi, 2 peteşi, 3 ekimoz, 4 subkonjuktival kanama, 5 üst gastrointestinal kanama, 6,7 perioperatif kanama, 7 vajinal kanama, 4 postpartum kanama 8 ve hematüri 2 şeklinde kanama bozukluklarına neden olduklarını gösteren birçok çalış-ma ve olgu bildirimi vardır. Ekimoz şeklinde ortaya çıkan kanama bozuklukları sertralin, 4 fluoksetin, 9 paroksetin 10 ve fluvoksamin 11 kullanımı sonrasında bildirilmiştir.…”
Section: ____________________________________________________________unclassified
“…It has been estimated that upper gastrointestinal bleeding occurs at 1 in 100 to 1 in 1,000 patient-years of exposure to high-affinity drugs (the SSRIs), with the very old patients being at the highest risk. The increased risk may be of particular relevance when the SSRIs are associated with nonsteroidal anti-inflammatory drugs (NSAIDs), as well as low-dose aspirin 1 . Bleeding from the upper gastrointestinal tract, caused by the SSRIs may appear through the SSRI induced inhibition of serotonin reuptake from platelets, leading to platelet serotonin depletion after several weeks of treatment.…”
Section: Introductionmentioning
confidence: 99%